Psychometric properties of the Parma Scale for the treatment evaluation of offenders with mental disorder: A new instrument for routine outcome monitoring in forensic psychiatric settings. (September 2022) - Pelizza, Lorenzo; Paulillo, Giuseppina; Maestri, Davide; Paraggio, Cecilia; De Amicis, Ilaria; Mammone, Elena; Scarci, Melania; Leuci, Emanuela; Pupo, Simona; Pellegrini, Pietro
Abstract: Purpose: Routine Outcome Monitoring (ROM) is still poorly implemented in the routine forensic psychiatric practice. As reliable ROM instruments are lacking, the aims of this research was to assess the psychometric properties of the Parma Scale (Pr-Scale) and its sensitivity to measure scores' longitudinal changes. Methods: Interrater and test-retest reliability, internal consistency and concurrent validity were investigated in offenders with mental disorder. Scores' longitudinal changeability was examined after a 3-month period using the Wilcoxon test for repeated measure. Results: Sixty male adult patients were recruited in this study. Our findings showed good to excellent interrater and test-retest reliability, concurrent validity and internal consistency for the Pr-Scale. Pr-Scale scores also display a moderate to large changeability over time. Conclusions: Our results support the clinical use of the Pr-Scale in forensic psychiatric settings as reliable ROM instrument. Highlights: The Parma Scale (Pr-Scale) was designed as routine outcome measure instrument for forensic psychiatric practice. Its interrater and test-retest reliability is good to excellent in Italian forensic psychiatric sample. Its internal consistence and concurrent validity are also god to excellent. The Pr-Scale scores also display a moderate to large changeability over time. The Pr-Scale is a reliable routine outcome measure instrument for different forensic psychiatric settings.